WAYS AND METHODS USED FOR THE DEVELOPMENT OF FORCE IN SWIMMING PARANAENSE (Fiep Bulletin - online, 2015)
The force work must inside be crucial of a took time of training swimming velocities and to know which is the half one more indicated to get resulted, it must influence in positive way in some aspects of paranaense swimming. The present characterized study as research of field and exploratory it has for objective to diagnosis the ways and methods used for the technician to develop the force in velocities athletes of swimming. The population shows is formed by 84,6% of the technician (N=11) of 90,9% of the swimmers (N=40) of the masculine sort who had reached one, it enters the three first ranks in the State Championships of Winter, of Summer and in the Open Games Paranaense in the year of 2004 in the categories Junior I, Junior II and Senior. The used instrument of research was a questionnaire structuralized with open and closed questions. Of the gotten results the force work is considered very important by the technician and that the application of this is carried through habitually by they themselves or for a professor of musculation guided or not for the technician. Main half of work used for attainment of force in the paranaenses velocity swimmers, for unanimity, it is the musculation work. However, most of the technician of water inside mix this work with specific methods for training of the force, as the time of the took time. Through this work it is possible to affirm that the force work is essential for a velocity swimmer, mainly when combined with an adequate work of training in the water and with the had respect to the periods of burnishing that precede an important competition.
Keywords: ways and methods; force work; swimming.